Effects of dietary Persian oak (Quercus brantii var. persica) fruit extract on survival, growth performance, haematological and immunological parameters in rainbow trout, Oncorhynchus mykiss, fingerlings. (14th February 2015) - Bohlouli, S.; Ghaedi, G.; Heydari, M.; Rahmani, A.; Sadeghi, E.
Abstract: The aim of study was to evaluate the effects of jaft (internal layer of oak fruit) extract on growth, haematological and immunological parameters in rainbow trout fingerlings. A total of 360 fish (average weight 6.25 g, total length 7.75 cm) were randomly distributed in 12 fibreglass tanks (stocking density: 1.04 g L −1 ) with flow rate of 8 L min −1 . The ethanolic extraction of jaft was taken, and, then, a basal diet was supplemented with 0 (control), 0.5, 1 and 2 g kg −1 to formulate four experimental diets. After 8 weeks, blood sampling was performed for haematological and immunological parameters. While immunological parameters such as IgM and lysozyme showed their lowest level in control group, their highest amounts appeared in 2 g kg −1 group. C3, C4 and alternative complement activity increased in fish fed 2 g kg −1 extract compared to control ( P  ˂ 0.05). Haematological parameters such as white blood cell, red blood cell, haemoglobin and haematocrit were enhanced in experimental groups ( P  ˂ 0.05). Survival and growth indices did not show significant changes in experimental treatments ( P  ˃ 0.05). Results indicated feeding rainbow trout with Persian oak extract at 0.5, 1.0 and 2.0 g kg −1 levels significantly enhance the immunological parameters.